Single real estate developers’ innovations in housing design: an historical exploration based on China Vanke Co. Ltd. - Carota, Francesco (Journal of Architecture and Urbanism, 2025)
This paper focuses on the practices, innovations and design regarding housing supply developed by a single Chinese private real estate company, China Vanke Co. Ltd. between 1979 and 2016. In the last 5 decades, China experienced a period of rapid urbanization, accompanied by the introduction of numerous economic and institutional reforms impacting the nation’s model of housing supply. Significant changes disrupted the urban housing sector in the country, shifting the main supply system from a public welfare model to a market-driven one. Within this time span, most new residential properties were developed and marketed by large real estate enterprises, which became crucial players in establishing the new housing market. While there is an extensive body of literature examining China’s housing market formation and progression, most of these studies focus on the economic and social aspects of housing, including factors such as affordability, inequality, governance, preferences and choices. Single real estate firms’ innovations, as well as the links between housing designs and market supply and demand, have yet to be thoroughly explored. This latter area represents thus the main focus of this paper. Expanding from the specific case of Vanke, this paper seeks to discuss the innovative processes of a real estate enterprise and the role of a single company in shaping new housing designs, based on supply and demand transformations.